Pengaruh Pemberian Ekstrak Kulit Manggis (Garcinia Manggostana Linn) sebagai Penurun Lipid pada Tikus Model Dislipidemia - Elok Erlita Nur Farradina; I Isbandiyah; Djanggan Sargowo (The Indonesian Heart Association, 2012)
Background. Dyslipidemia is a risk factor of atherosclerosis, characterized by increase total cholesterol (TC), trigliserida (TG), Low Density Lipoprotein (LDL) and decrease of High Density Lipoprotein(HDL). Previous study showed positive correlation between dyslipidemia with severity of atherosclerosis. Effect of pericap mangosteen contains Xanthonepresumed could decreased the total cholesterol (TC), triglyceride (TG), and Low Density Lipoprotein(LDL) levels and increased High Density Lipoprotein(HDL) level from the blood of white mice by activated the path of reverse cholesterol transport.Purpose. To prove that extract from pericap mangosteen decrease LDL, triglyceride, total cholesterol and increase HDL.Methode. Laboratory experiment with the post test only control group design. The samples strain wistar white rats were devided into 5 groups. The sample I : Negative control, II : Positive control and the threeother groups were treated by extract from pericap mangosteen with variouse doses (200mg/day, 400mg/day, 800 mg/day). The data were analyzed by One Way Anova, Tukey test 5%, correlation test and linear regression test.Result. The result of this observation showed that efective dose of extract of pericap mangosteento decrease TC, TG and LDL level and increase HDL level is 800 mg/day. TC lowering in group were trea ted with extract from pericap mangosteen 200mg/dayis= 39,667 400mg/day = 27,833 800mg/day = 19,333. TG lowering in group were treated with extract from pericap mangosteen 200mg/dayis = 40,333 400mg/day = 34,333 800mg/day = 26,667. LDL lowering in group were treated with extract from pericap mangosteen 200mg/dayis = 45,433400mg/day = 32,467 800mg/day = 14,733. HDL raising in group were treated with extract from pericap man gosteen 200mg/day is = 13,833400mg/day = 11,500 800mg/day = 3,000.Coclusion. Oral administration (200, 400 dan 800 mg/day) of extract from pericap of mangosteen decreasing LDL, trygliseride, total cholesterol and increasing HDL of dyslipidemia male white rate.